Antiprotozoal Drug Handling and Management Practices in Asella District, Central Oromia, Ethiopia - Ashenafi Ababu; Dereje Endashaw; Haben Fesseha; Mesfin Mathewos (Veterinary Medicine International)
Background and Methods. Protozoal infections such as dourine caused by trypanosomes are found to be a threat to the life and productivity of the equine population. Inappropriate drug use is a problem of the whole world; however, the degree of the problem is higher in developing countries like Ethiopia. Data on handling and management practices of antiprotozoal drugs are not in place; thus, we estimate the handling and management practice via a simple cross-sectional study design in randomly selected veterinary clinics and private pharmacies in and around Asella, Oromia, central Ethiopia. Results. The preliminary survey comprising 70 animal health professionals and animal owners was undertaken through observation, interview using a structured questionnaire, and discussion with key informants to evaluate their handling and management practices of antiprotozoal drugs. According to the finding of this preliminary survey, there was inadequate antiprotozoal drug distribution and only few drugs, namely, diminazene diaceturate, amprolium, and sulfa drugs, were available with different trade names being imported from different manufacturing countries. Among the current available antiprotozoal drugs circulating in the area, those manufactured and imported from China were highly distributed in the majority of veterinary drug shops. The assessment showed that there was a gap in achieving the required knowledge and practice of proper handling and management issues in the professionals and awareness problems in the community. The study indicated that there were inappropriate transportation and storage practices. Moreover, selling drugs without prescription, ignoring farmers without properly informing the drug withdrawal period, and administration of drugs by nonprofessionals were the other most critical and unethical practices in the area. It is emphasized that this inappropriate handling and management practice, scarcity of antiprotozoal drugs, easy accessibility, and distribution by nonprofessionals could potentially affect the quality, safety, and effectiveness of antiprotozoal drugs which may lead to drug resistance development. Conclusion. Hence, continuous awareness creation in the community, capacity building, training, and upgrading programs to the professionals, as well as strict enforcement of drug control and administration regulation of the country, are essential in the overall effort of improving animal health and productivity through the control of protozoan diseases in and around Asella.